Extraction of Antioxidant, Flavonoids and Phenolic content from N. Sativa - Nur Farahin, Ishak; Sook, Fun Pang; Noor Intan Shafinas, Muhammad; Nuraini, Mohd Yusoff; Mohd Arman, Abd Kadir; Sazwani, Suhaimi; Hafizah, Ramli; Mohd Faried, Abdullah; Zainal, Giman; Jolius, Gimbun (2013)
Nigella sativa commonly known as habbatus sauda belongs to a botanical family of Rununculaceae. The N. sativa seed is rich with medicinal value and has been used as a natural remedy since ancient time by people in Mediterranean region. Previous research revealed it contained an abundance of active ingredients useful for anticancer and anti-inflammatory, anti-dermatopyhte, asthma, hypertension, diabetes, cought, bronchitis, fever, dizziness and gastrointestinal disturbances.